Assessment of functional capacity and the risk of falls in the elderly with mild and moderate stage dementia - Skubal, Anna; Sudoł, Izabela; Ciąpała, Gabriela; Ćwirlej-Sozańska, Agnieszka; Wiśniowska-Szurlej, Agnieszka; Wilmowska-Pietruszyńska, Anna (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction: Dementia is a common problem among the elderly. Cognitive impairments may cause difficulty in performing basic activities of daily living. The deterioration of physical and / or mental capacity can lead to the necessity of institutional care over patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim: To assess functional capacity and the risk of falls in the elderly with mild and moderate dementia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and Methods: The study group included 146 people aged 60-90 residing in the Residential Home as well as Care and Treatment Centre in the south-eastern Poland. Cognitive and functional capacity, balance, and the risk of falls were assessed using the following scales and clinical tests: the Mini-Mental State Examination (MMSE), Geriatric Depression Scale (GDS), Activities of Daily Living (ADL), Time Up & Go test, Tinetti test, Berg Balance Scale. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: It has been demonstrated that individuals with dementia were characterized by reduced capacity in performing basic activities of daily living. More than half of the patients with mild and moderate dementia presented 5-times higher risk of falls than those without dementia. Moderate risk of falls was observed in 76.1% of patients with moderate dementia. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: Cognitive impairments decrease the capacity to perform basic activities of daily living. The higher the stage of dementia, the worse the balance and the greater the risk of falling. It is necessary to develop simple rehabilitation programs allowing to maintain the highest possible level of functional capacity in the elderly patients with dementia under institutional care.